Taxing the Bilingual Mind: Effects of Simultaneous Interpreting Experience on Verbal and Executive Mechanisms - Muñoz-Arias, E (Cambridge University Press, 2020)
This paper reviews the neurocognitive particularities of subjects with sustained experience in simultaneous interpreting, a highly demanding form of bilingual processing. The literature converges into three broad empirical patterns. First, significant neurocognitive differences, including behavioral enhancements in verbal and executive domains, are observable after only one or two years of training. Second, such effects, both in interpreting students and/or professional interpreters, seem robust for crucial linguistic (e.g., translation) and executive (e.g., working memory) aspects of the activity, but not for more marginally relevant ones (e.g., conflict resolution)-suggesting that they are non-generalizable beyond directly taxed functions. Third, though more tentatively, some of the observed verbal and executive effects seem to be mutually independent and uninfluenced by other bilingual-experience-related factors (e.g., L2 competence), which could highlight their distinctive relation with interpreting practice. In sum, this particular model of expertise sheds novel light on the adaptive capacity of cognitive systems in bilinguals. Copyright © 2019 Cambridge University Press.